Pengaruh Return On Assets, Ukuran Perusahaan, Kompensasi Rugi Fiskal, Dan Kepemilikan Institusional Terhadap Tax Avoidance - Annisa Alfahira Zaenuddin; Dyarini Binti Thamrin (Jurnal Akuntansi dan Governance, 2023)
This study aims to analyze the effect of Return on Assets (ROA), firm size, fiscal loss compensation, and institutional ownership on tax avoidance. The population is the mining industry whose shares are traded on the Indonesia Stock Exchange (IDX) between 2016 and 2020. And with a purposive sampling technique, 80 samples were selected. By using multiple linear regression, the results show that ROA, firm size, fiscal loss compensation, and institutional ownership simultaneously had an insignificant positive effect on tax avoidance. Partially, ROA and firm size have a significant negative effect on tax avoidance; while compensation for fiscal losses has no significant positive effect, and institutional ownership has a significant negative effect on tax avoidance